2017
DOI: 10.24297/jac.v5i3.6592
|View full text |Cite
|
Sign up to set email alerts
|

Defluoridation of South Tunisian Brackish Water by Alum Coagulation/Flocculation: A Preliminary Work

Abstract: Fluoride removal from aqueous solution was investigated using the chemical coagulation-flocculation by alum in reason of the efficiency and the simplicity of the process. Preliminary experiments were carried out to study the effect of some operating parameters such as: pH, initial fluoride concentration, coagulant dose, adjuvant coagulation dose, flocculent dose and settling time. Obtained experimental results showed that the treatment of fluoride by alum coagulation causes acidification of the solution. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In a study by Missaoui on EC treatment for fluoride removal from brackish water, the removal efficiency up to 52% was achieved under optimal status [67]. e study by Chibania et al reported the fluoride removal of over 85% in 20 min using EC technique [36].…”
Section: Electrocoagulation (Ec)mentioning
confidence: 99%
“…In a study by Missaoui on EC treatment for fluoride removal from brackish water, the removal efficiency up to 52% was achieved under optimal status [67]. e study by Chibania et al reported the fluoride removal of over 85% in 20 min using EC technique [36].…”
Section: Electrocoagulation (Ec)mentioning
confidence: 99%
“…High quantities of fluorides are often found in groundwater from the captive aquifers of phosphate-producing countries. Fluoride poses public health problems, for example in India, where research with CEFIRES [2] [3] is available, but also in Senegal, China, Russia, the United States, etc. In countries, such as the United States, the Commonwealth of Independent States, North Africa and West Africa, including Senegal, the fluorides attributed to fluorine ores (fluoroapatite) are generally due to the presence of phosphates (hydroxyapatite).…”
Section: Introductionmentioning
confidence: 99%